Analysis of phylogenetic relationships in Macadamia shows evidence of extensive reticulate evolution - Manatunga, Sachini Lakmini; Furtado, Agnelo; Topp, Bruce; Alam, Mobashwer; Mason, Patrick J.; Kharabian-Masouleh, Ardashir; Henry, Robert J. (Frontiers in Plant Science, 2024)
The genus Macadamia in the Proteaceae family includes four species native to Australia. Two of the four species M. integrifolia and M. tetraphylla have recently been utilized to generate domesticated macadamia varieties, grown for their edible nuts. To explore diversity in macadamia genetic resources, a total of 166 wild genotypes, representing all four species, were sequenced. The four species were clearly distinguished as four separate clades in a phylogenetic analysis of the nuclear genome (based upon concatenated nuclear gene CDS). The two larger species (M. integrifolia and M. tetraphylla) formed a clade that had diverged from a clade including the smaller species (M. ternifolia and M. jansenii). The greatest diversity in nuclear and chloroplast genomes was found in the more widely distributed M. integrifolia while the rare M. jansenii showed little diversity. The chloroplast phylogeny revealed a much more complex evolutionary history. Multiple chloroplast capture events have resulted in chloroplast genome clades including genotypes from different species. This suggests extensive reticulate evolution in Macadamia despite the emergence of the four distinct species that are supported by the analysis of their nuclear genomes. The chloroplast genomes showed strong associations with geographical distribution reflecting limited maternal gene movement in these species having large seeds. The nuclear genomes showed lesser geographical differences, probably reflecting longer distance movement of pollen. This improved understanding of the distribution of diversity in Macadamia will aid conservation of these rare species now found in highly fragmented rainforest remnants.